PENGARUH JUMLAH PERSEDIAAN BAHAN BAKU DAN KAPASITAS MESIN TERHADAP VOLUME PRODUKSI PADA UD. CAHAYA RESTU KOTA PROBOLINGGO - Dedi Joko Hermawan (CAPITAL: Jurnal Ekonomi dan Manajemen, 2018)
ABSTRACTThe objective of this study was for determine and analyze the effect of the amount of raw material inventory and engine capacity simultaneously to volume production at UD. Cahaya Restu. The population of this research is all company data on the number of inventories of raw materials, machine capacity and production volume in 2011-2016 at UD.Cahaya Restu. The collection of data through observation. The data used in this research is secondary data in the form of a company's internal data UD. Cahaya Restu, Based on the results of multiple regression analysis and hypothesis testing by using test of F can be seen that simultaneously the number of inventories of raw materials (X1) and engine capacity (X2) significantly affects the volume of production (Y). While based on the hypothesis test by using test tcount that the partial amount of raw material inventory (X1) there is a significant effect on the volume of production (Y) and the capacity of the machine (X2) partially no significant effect on the volume of production (Y).Keywords: the number of inventories of raw materials, machine capacity, and volume production